Pengaruh Mindfulness Terhadap Regulasi Emosi Pada Siswa Kelas VII SMP Negeri 5 Semarang - Novia Meylana Ruhmi; Suhendri Suhendri; Padmi Dhyah Yulianti (Indonesian Journal of Educational Counseling, 2026)
Emotional regulation is an essential ability for junior high school students, particularly during early adolescence, a developmental stage marked by emotional, social, and academic changes. One factor that may influence emotional regulation is mindfulness, defined as the ability to be fully aware of present experiences without judgment. This study aimed to examine the effect of mindfulness on emotional regulation among seventh-grade students at SMP Negeri 5 Semarang. This research employed a quantitative approach with an ex post facto design. The population consisted of 288 students, and 140 students were selected as the sample through cluster random sampling. Data were collected using mindfulness and emotional regulation scales and analyzed using simple linear regression with SPSS version 26. The results showed that mindfulness had a positive and significant effect on emotional regulation (β = 0.605; p < 0.05). The coefficient of determination (R Square) was 0.169, indicating that mindfulness contributed 16.9% to students’ emotional regulation, while the remaining 83.1% was influenced by other factors. These findings suggest that higher mindfulness is associated with better emotional regulation. Therefore, schools are encouraged to develop mindfulness-based programs to support students’ emotional development.